Resistance in tuberculosis: what do we know and where can we go? - Green, Keith; Garneau-Tsodikova, Sylvie (Frontiers in Microbiology, 2013)
Tuberculosis (TB) has become a worldwide threat, mainly due to the emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of Mycobacterium tuberculosis (Mtb). This mini-review is focused on the various mechanisms of resistance to the currently available anti-TB drugs and provides perspective on novel strategies and lead scaffolds/compounds aimed at inhibiting/overcoming these resistance mechanisms.